2007
DOI: 10.2135/cropsci2005.07.0346er
|View full text |Cite
|
Sign up to set email alerts
|

Crop Rotation and Soil Amendment Alters Sorghum Grain Quality

Abstract: Soybean [Glycine max (L.) Merr.] rotation enhances grain sorghum [Sorghum bicolor (L.) Moench] yield, but infl uence on grain quality has not been measured. The objective was to determine the effect of cropping sequence (CS) and soil amendment (SA) on grain yield and quality. Sorghum grain yield and quality, soil NO 3-N and water were measured in a rotation study in 2003 and 2004 on a Sharpsburg silty clay loam (fi ne, smectitic, mesic Typic Argiudoll). Cropping sequences were continuous sorghum, and sorghum r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 12 publications
4
10
1
Order By: Relevance
“…Sorghum responded similarly to the different management systems; compared with the average of two conventional systems the OAM system yielded 84% and the OFG system yielded 73%. The greater sorghum yields in the OAM system compared to the OFG system are similar to the results of Mady Kaye et al 10 , who observed an 8% increase in sorghum yields when amended with manure and rotated with soybean.…”
Section: Crop Yieldssupporting
confidence: 88%
See 1 more Smart Citation
“…Sorghum responded similarly to the different management systems; compared with the average of two conventional systems the OAM system yielded 84% and the OFG system yielded 73%. The greater sorghum yields in the OAM system compared to the OFG system are similar to the results of Mady Kaye et al 10 , who observed an 8% increase in sorghum yields when amended with manure and rotated with soybean.…”
Section: Crop Yieldssupporting
confidence: 88%
“…Additionally, organic cropping systems often rely on organic soil amendments such as farmyard manure or compost. Both crop rotation and manure amendments have been shown to improve grain yield compared with continuous cropping systems with synthetic fertilizers 10 . Moreover, organic soil amendments have been associated with improved soil properties such as increased soil organic matter content (OMC) and water-holding capacity, lower bulk density and enhanced pH stabilization 3,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…Kernel weight (P < 0.001) and density (P < 0.0001) were positively correlated with starch contents but strongly and negatively (P < 0.0001) correlated with protein contents (Table III). Kernel test weight and true density were positively associated with grain yield (Kaye et al 2007). Ethanol yield was greatly affected by kernel test weight and true density (P < 0.0001) (Table III), which agreed with the effects of irrigation level on ethanol yield.…”
Section: Effects On Physical Properties and Chemical Composition Of Msupporting
confidence: 74%
“…Kernel test weight was positively (p < 0.0001) correlated with starch contents but negatively (p < 0.001) correlated with protein contents. Kaye et al (2007) reported that kernel test weight was positively associated with grain yield. Ethanol yield was found to be greatly affected by kernel test weight (p < 0.0001), which agreed with the effects of irrigation level on ethanol yield.…”
Section: Physical Properties and Chemical Compositionmentioning
confidence: 99%